Critical Review of Advances and Numerical Modeling in Absorbers and Desorbers of Absorption Chillers: CFD Applications, Constraints, and Future Prospects - Suellen Cristina Sousa Alcântara; José Ângelo Peixoto da Costa; Alvaro Antonio Villa Ochoa; Gustavo de Novaes Pires Leite; Álvaro Augusto Soares Lima; Héber Claudius Nunes Silva; Paula Suemy Arruda Michima; Igor Cavalcanti da Silveira; Allysson Macário de Araújo Caldas; Amín Altamirano (Energies)
This article critically reviews advances and numerical modeling in absorbers and desorbers used in absorption refrigeration systems, emphasizing the applications, limitations, and future perspectives of computational fluid dynamics (CFD). This study’s main contribution lies in the detailed and critical analysis of the use of CFD in physical models of absorbers and generators of absorption chillers. In addition, several heat exchanger technologies, such as falling film, membranes, and bubbling, are addressed, highlighting CFD-based studies’ main findings and challenges. The article also explores the integration of artificial intelligence (AI) in CFD analyses, aiming to optimize modeling and system performance. It was found that the application of CFD analyses in absorbers and desorbers of absorption systems has proven to be an essential tool for developing and optimizing these systems. Finally, research gaps were identified, especially regarding the miniaturization and optimization of these exchangers, and directions for future studies are proposed.